A Controlled Challenge Study on Di(2-ethylhexyl) Phthalate (DEHP) in House Dust and the Immune Response in Human Nasal Mucosa of Allergic Subjects - Deutschle, Tom; Reiter, Rudolf; Butte, Werner; Heinzow, Birger; Keck, Tilman; Riechelmann, Herbert (Environmental health perspectives, 2008)
Background: Few studies have yet addressed the effects of di(2-ethylhexyl) phthalate (DEHP) in house dust on human nasal mucosa. Objectives: We investigated the effects of house dust containing DEHP on nasal mucosa of healthy and house dust mite (HDM)-allergic subjects in a short-term exposure setting. Methods: We challenged 16 healthy and 16 HDM-allergic subjects for 3 hr with house dust at a concentration of 300 μg/m³ containing either low (0.41 mg/g) or high (2.09 mg/g) levels of DEHP. Exposure to filtered air served as control. After exposure, we measured proteins and performed a DNA microarray analysis. Results: Nasal exposure to house dust with low or high DEHP had no effect on symptom scores. Healthy subjects had almost no response to inhaled dust, but HDM-allergic subjects showed varied responses:${\rm DEHP}_{\text{low}}$house dust increased eosinophil cationic protein, granulocyte-colony-stimulating factor (G-CSF), interleukin (IL)-5, and IL-6, whereas${\rm DEHP}_{\text{high}}$house dust decreased G-CSF and IL-6. Furthermore, in healthy subjects, DEHP concentration resulted in 10 differentially expressed genes, whereas 16 genes were differentially expressed in HDM-allergic subjects, among them anti-Müllerian hormone, which was significantly up-regulated after exposure to${\rm DEHP}_{\text{high}}$house dust compared with exposure to${\rm DEHP}_{\text{low}}$house dust, and fibroblast growth factor 9, IL-6, and transforming growth factor-β1, which were down-regulated. Conclusions: Short-term exposure to house dust with high concentrations of DEHP has attenuating effects on human nasal immune response in HDM-allergic subjects, concerning both gene expression and cytokines.